2017
DOI: 10.1088/1361-6528/aa655c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of self-assembled nanoscale graphene/graphene oxide photomemristive heterojunctions using photocatalytic oxidation

Abstract: Photocatalytic oxidation of graphene with ZnO nanoparticles was found to create self-assembled graphene oxide/graphene (G/GO) photosensitive heterostructures, which can be used as memristors. Oxygen groups released during photodecomposition of water molecules on the nanoparticles under ultraviolet light, oxidized graphene, locally forming the G/GO heterojunctions with ultra-high density. The G/GO nanostructures have non-linear current-voltage characteristics and switch the resistance in the dark and under whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…O. O. Kapitanova et al [58] exploited the photocatalytic oxidation of graphene to generate graphene/graphene oxide (G/GO) photosensitive heterostructures, which could be used as memristors. Photoactive ZnO nanoparticles were deposited on multilayer graphene, which was then irradiated with UV light (≤365 nm, 0.03 J min −1 cm −2 ) under a flow of humid air for different times (from 5 to 90 min) at different temperatures (room temperature or 80 • C).…”
Section: Patterning Of Graphene and Graphene Oxidementioning
confidence: 99%
“…O. O. Kapitanova et al [58] exploited the photocatalytic oxidation of graphene to generate graphene/graphene oxide (G/GO) photosensitive heterostructures, which could be used as memristors. Photoactive ZnO nanoparticles were deposited on multilayer graphene, which was then irradiated with UV light (≤365 nm, 0.03 J min −1 cm −2 ) under a flow of humid air for different times (from 5 to 90 min) at different temperatures (room temperature or 80 • C).…”
Section: Patterning Of Graphene and Graphene Oxidementioning
confidence: 99%
“…The mechanism of resistive switching in G/GO was studied in detail in a number of works [12][13][14][15][16][17] in which it was shown that the migration of oxygen-containing groups in GO plays an important role. One sp 3 carbon-oxygen or carbon-hydroxyl bond on 10 6 sp 2 bonds reduced conductivity in carbon nanomaterials by 50% [18].…”
Section: The Mechanism Of Resistive Switching In Graphene/graphene Oxidementioning
confidence: 99%
“…The photocatalytic oxidation of graphene coated with a layer of 10-15 nm ZnO nanoparticles under ultraviolet (UV) irradiation conditions led to the formation of self-organized G/GO memristors with very high density (10 12 cm −2 ) [16,17]. Figure 7 shows the scheme of photocatalytic oxidation of graphene with ZnO nanoparticles.…”
Section: Self-organization Of Memristors Based On Graphene/graphene Omentioning
confidence: 99%
See 1 more Smart Citation
“…The unique electronic and optical properties of graphene oxide demonstrate a huge potential for designing ultrahigh density memristive elements to be used as interfaces with electronic artificial neural networks. The different degree of reduction/oxidation of graphene oxide/graphene allows monitoring multiple memristive states in a wide spectral range by using electric and optic excitation [15]. Non-volatile resistive memory (NVM) devices allow creation of efficient systems for analog and neuromorphic computation in the field of large data and artificial intelligence [16].…”
Section: Introductionmentioning
confidence: 99%